2022
DOI: 10.1021/acs.jpcc.1c08651
|View full text |Cite
|
Sign up to set email alerts
|

Potential-Dependent Interfacial Frictional Behavior between Charged Microspheres and Gold in Aqueous Solutions

Abstract: We study the interfacial frictional behavior between negatively charged hydroxyl- and carboxyl-functionalized and positively charged amino-functionalized colloidal probes and a gold electrode (GE) through electrochemical atomic force microscopy. The charged microspheres exhibit similar potential-dependent frictional behavior, with high and low frictional forces at positive and negative gold potentials, respectively. However, normal force and X-ray photoelectron spectroscopy revealed that the oppositely charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Experimental results from a surface force apparatus (SFG) and AFM indicate that under positive potentials in the electrolyte, a viscous ice-like water layer forms on the gold surface [76][77][78][79]. Pashazanusi and Li et al [33,34,[80][81][82] proposed that strong hydrogen bonding between this ice-like water layer and the polar friction materials accounts for the high friction. Thus, the tribological mechanism of potential modulation on gold surfaces in salt solutions warrants further investigation.…”
Section: Adsorption Of Surface Hydrated Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental results from a surface force apparatus (SFG) and AFM indicate that under positive potentials in the electrolyte, a viscous ice-like water layer forms on the gold surface [76][77][78][79]. Pashazanusi and Li et al [33,34,[80][81][82] proposed that strong hydrogen bonding between this ice-like water layer and the polar friction materials accounts for the high friction. Thus, the tribological mechanism of potential modulation on gold surfaces in salt solutions warrants further investigation.…”
Section: Adsorption Of Surface Hydrated Ionsmentioning
confidence: 99%
“…The adhesion and friction between interfaces under a positive potential are primarily attributed to the hydrogen bonding force between the ice-like water layer and the hydroxyl groups on the SiO 2 surface, as illustrated in Figure 11. Recently, Li et al [82] also identified differences in hydrogen bonding mechanisms between positive microspheres (−NH 3 terminal microspheres) and negative microspheres (−OH and −COOH terminal microspheres) and the ice-like water layer. Negative microspheres directly form hydrogen bonds with the ice-like water layer through surface polar groups, while positive microspheres generate hydrogen bond sets with the ice-like water layer through hydrating anions adsorbed on the surface within their hydration shell.…”
Section: Phase Structure Transformation Of Water Moleculesmentioning
confidence: 99%
“…[1][2][3][4] In particular, the tuning role of applied electric fields in confined geometries has been widely investigated in triboelectrochemistry experiments. [5][6][7][8][9][10][11][12][13] In most of these experiments ions move in a liquid solution driven by the applied field, covering and effectively modifying the sliding surfaces, thus inducing changes in friction. [14][15][16][17][18][19][20][21][22] An alternative approach is based on the ability of the electric field to reorient macromolecules, thus changing their conformation in aqueous solution [23][24][25] and dry environments, [26][27][28] with potentially dramatic effects on friction.…”
Section: Introductionmentioning
confidence: 99%